El (contra-)archivo de la Abadía del Sacromonte y las incursiones del gobernador Cristóbal Vaca de Castro ante la justicia del rey - Roy, Hélène (2022)
In this contribution, we offer to analyze the archivistic context in which the oldest colonial archives of the Sacromonte Abbey are preserved as a result of a project of family autopromotion aimed at opposing the King's justice and the official history. We will show how archives can be used as instruments of counter-legitimacy. This case will be dealt with according to two axes of research, the first being the archival turn which considers archives as a result of «non-innocent» operations of archival collection, selection, organization and uses. The second axis is linked to the political history of the Spanish monarchy, lately dominated by case studies which shed light on the loyalty of royal agents and the justice administration as the pillars of imperial power.